Peripheral neuromuscular fatigue induced by repeated-sprint exercise: cycling vs. running - Rampinini, E.; Connolly, D. R.; Ferioli, D.; La Torre, A.; Bosio, A. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: Peripheral fatigue in knee extensor (KE) and plantar flexor (PF) muscles were investigated following repeated-sprint ability (RSA) cycling and running tests. METHODS: Both RSA tests involved 5x6 s sprints and peripheral fatigue was quantified using diverse electrical stimulations (1Hz, 10Hz, 20Hz, 50Hz and 100Hz). RESULTS: RSA cycling induced higher KE decrements in peak torque (PT), maximal rate of torque development and relaxation (PT decrements at different stimulation frequencies: from -39% to -53% cycling vs. -16% to -39% running, P0.231); however, greater reductions in some PT ratios (10/100 Hz, 20/50 Hz and 20/100 Hz) confirmed the presence of low-frequency fatigue in PF following RSA cycling. Subjects reported significantly higher RPE leg values following RSA cycling (8.2 vs 7.3 respectively, P=0.018) despite no differences in blood lactate, hydrogen ions and bicarbonates (P>0.467). CONCLUSIONS: Higher levels of peripheral fatigue induced by RSA cycling may be partially related to longer fractional duration of muscle contraction phases that can limit local blood flow. The discrepancies in neuromuscular fatigue between KE and PF can be explained by differences in muscle fibre composition or muscle contributions during RSA tests.